Self-Esteem and Social Support are Needed to Increase the Resilience of Student's Mothers - Choiril Anwar; Nikmah Rochmawati; Dewi Khurun Aini (Sawwa: Jurnal Studi Gender, 2022)
Resilience is essential for mothers who experience pressure and stress while accompanying their children to take part in distance learning during the COVID-19 pandemic. This study aims to empirically examine the effect of self-esteem and social support on mothers’ resilience of Early Childhood Education students during distance learning assistance. This quantitative study uses a sample of 117 mothers of Early Childhood Education students in Bulusari Village, Sayung District, Demak Regency. The sampling technique used is non-probability sampling with a convenience sampling method. The measuring instrument of this study consisted of a self-esteem scale, a social support scale, and a resilience scale with data collection techniques through questionnaires. The data analysis method in this study used multiple linear regression analysis. The study’s results showed that self-esteem and social support simultaneously significantly affected resilience with a significance value of 0.000 0.05 with a contribution of 41.3%. It proves that self-esteem and social support empirically have a role in the resilience of mothers of Early Childhood Education students during distance learning assistance.